Pengembangan Formulasi Tablet Karbon Aktif Kayu Gelam (Melaleuca Sp) sebagai Alternatif Pengobatan Antidiare - Tuti Alawiyah; Raihanah Raihanah; Setia Budi; Sismeri Dona (Journal of Pharmaceutical and Sciences, 2026)
Background: Diarrhea remains a major global health problem requiring effective and safe therapeutic interventions. The utilization of natural activated carbon presents a promising alternative for antidiarrheal therapy. Objective: This study aimed to develop an activated carbon tablet formulation derived from Kayu Gelam (Melaleuca sp.) and to evaluate the physical and chemical quality of the resulting tablets. Methods: Activated carbon was obtained through carbonization and chemical activation processes, then formulated into three tablet formulas with varying concentrations of polyvinylpyrrolidone (PVP) as a binder: 2% (Formula 1), 3% (Formula 2), and 4% (Formula 3). Tablet quality evaluation included pH measurement, weight uniformity, hardness, friability, and disintegration time. Data were analyzed using one-way ANOVA. Results: The pH values of Formulas 1, 2, and 3 were 6.15, 6.65, and 6.85, respectively, all within the neutral range (5.8–7.4) and safe for biological systems. The average tablet weights were 157.0 mg, 153.5 mg, and 158.5 mg, respectively, meeting weight uniformity requirements. Hardness values were 6.47 kg, 6.83 kg, and 7.67 kg, indicating adequate mechanical strength. Friability values were 0.664%, 0.763%, and 0.502%, all below the acceptable limit of 1%. Disintegration times were 13.01 min, 13.65 min, and 13.85 min, respectively, satisfying the requirement of less than 15 minutes. One-way ANOVA revealed significant differences (p < 0.05) in pH, hardness, friability, and disintegration time among the three formulas, while weight uniformity showed no significant difference (p > 0.05). Conclusion: All formulated Kayu Gelam activated carbon tablets met the required physical and chemical quality parameters, demonstrating their potential for further development as an alternative antidiarrheal tablet preparation.